Somatic Depolarization Enhances Hippocampal CA1 Dendritic Spike Propagation and Distal Input-Driven Synaptic Plasticity - Bock, Tobias; Negrean, Adrian; Siegelbaum, Steven A. (The Journal of neuroscience, 2022)
Synaptic inputs that target distal regions of neuronal dendrites can often generate local dendritic spikes that can amplify synaptic depolarization, induce synaptic plasticity, and enhance neuronal output. However, distal dendritic spikes are subject to significant attenuation by dendritic cable properties, and often produce only a weak subthreshold depolarization of the soma. Nonetheless, such spikes have been implicated in memory storage, sensory perception and place field formation. How can such a weak somatic response produce such powerful behavioral effects? Here, we use dual dendritic and somatic recordings in acute hippocampal slices of male mice to reveal that dendritic spike propagation, but not spike initiation, is strongly enhanced when the somatic resting potential is depolarized, likely as a result of increased inactivation of A-type K + channels. Somatic depolarization also facilitates the induction of a form of dendritic spike driven heterosynaptic plasticity that enhances memory specificity. Thus, the effect of somatic membrane depolarization to enhance dendritic spike propagation and long-term synaptic plasticity is likely to play an important role in hippocampal-dependent spatial representations as well as learning and memory. SIGNIFICANCE STATEMENT Neurons receive synaptic input along their dendrites but produce action potential (AP) output at their soma. Signals arriving at the distal dendrites of pyramidal neurons (PNs) have little impact on the soma unless they combine to initiate a dendritic spike, which needs to propagate to the soma to trigger an AP. This study shows that small subthreshold depolarization of the soma powerfully enhances the propagation of dendritic spikes, through inactivation of dendritic A-type potassium channels. Enhanced dendritic spike propagation also markedly facilitates the induction of a form of plasticity driven by the distal synaptic inputs. Thus, small changes in somatic membrane potential, similar to those observed in vivo , act as a powerful gate of neuronal information transfer.